High‐Performance Dual‐Salt Plastic Crystal Electrolyte Enabled by Succinonitrile‐Regulated Porous Polymer Host. (2nd February 2023) - Bao, Dequan; Tao, Yi; Zhong, Yihong; Zhao, Wei; Peng, Mingfa; Zhang, Hao; Sun, Xuhui
Abstract: Succinonitrile (SN)‐based plastic crystal electrolytes (PCE) show great promise for solid‐state lithium‐metal batteries (LMBs) because of their outstanding electrochemical properties. However, limited by the low mechanical strength of SN, SN‐based PCEs are difficult to act as an independent self‐supporting electrolyte films, which seriously restricts their practical application. In this study, a SN‐regulated poly(vinylidene fluoride‐co‐hexafluoropropylene) (PVDF‐HFP) porous host is proposed via a facile phase separation method as a promising strategy for addressing this issue, which enables a high‐performance dual‐salt SN‐based PCE (named as DPCE). The as‐prepared host simultaneously provides homogeneous porous network and robust mechanical support, which is convenient to accommodate DPCE evenly and increases the strength of DPCE to restrict dendrites growth. As a result, with this efficient host, the Li symmetric cell assembled with DPCE shows superior long‐term stability for >1200 h at a current density of 0.1 mA cm −2 . Moreover, the assembled Li|LiFePO4 cell delivers a high‐capacity retention of 99.3% after 700 cycles under 2 C at room temperature, demonstrating the promising potential for developing high‐performance solid‐state LMBs. Abstract : A poly (vinylidene fluoride‐co‐hexafluoropropylene) (PVDF‐HFP) porous host regulated by succinonitrile (SN) is fabricated via a facile phase separation method. The porous host simultaneously possesses a homogeneous porous network and robust mechanical support strength, which assists a dual‐salt SN‐based plastic crystal electrolyte in suppressing lithium dendrites formation. Consequently, the assembled lithium cells based on dual‐salt SN‐based electrolyte demonstrate superior cycling stability.